Analytical modeling and atlas simulation of N+-Hg0.69 Cd0.31Te /n0 Hg0.78 Cd0.22Te /p+-Hg0.78 Cd0.22Te p-i-n photodetector for long wavelength free space optical communication - Dwivedi A.D.D.; Chakrabarti P. (My University, 2025)
In this paper we report an analytical modeling of N+-Hg0.69 Cd0.31Te /n0 Hg0.78 Cd0.22Te /p+-Hg0.78 Cd0.22Te p-i-n photodetector for long wavelength free space optical communication. The results obtained on the basis of our model have been compared and contrasted with the simulated results using ATLAS™. The photodetector has been studied in respect of energy band diagram, electric field profile, doping profile, dark current, resistance area-product, quantum efficiency, spectral response, responsivity and detectivity by analytical method using closed form equations and also been simulated by using device simulation software ATLAS™ from SILVACO® international. The photodetector exhibits a high value of quantum efficiency ~80%, responsivity ~7 A/W, specific detectivity ~3.44×1011 mHz1/2W-1at wavelength10.6μm, dark current of the order of 10-11 A. The estimated noise equivalent power (NEP) is the order of 3×10-18 W.